High association of Cryptosporidium spp. infection with colon adenocarcinoma in Lebanese patients - Osman, Marwan; Benamrouz, Sadia; Guyot, Karine; Baydoun, Martha; Frealle, Emilie; Chabe, Magali; Gantois, Nausicaa; Delaire, Baptiste; Goffard, Anne; Aoun, Albert; Jurdi, Nawaf; Dabboussi, Fouad; et al. (PLOS ONE, 2017)
Background The association between Cryptosporidium and human colon cancer has been reported in different populations. However, this association has not been well studied. In order to add new strong arguments for a probable link between cryptosporidiosis and colon human cancer, the aim of this study was to determine prevalence and to identify species of Cryptosporidium among Lebanese patients. Methodology and principal findings Overall, 218 digestive biopsies were collected in Tripoli, Lebanon, from three groups of patients: (i) patients with recently diagnosed colon intraepithelial neoplasia/adenocarcinoma before any treatment (n = 72); (ii) patients with recently diagnosed stomach intraepithelial neoplasia/adenocarcinoma before any treatment (n = 21); and (iii) patients without digestive intraepithelial neoplasia/adenocarcinoma but with persistent digestive symptoms (n = 125). DNA extraction was performed from paraffin-embedded tissue. The presence of the parasite in tissues was confirmed by PCR, microscopic observation and immunofluorescence analysis. We identified a high rate (21%) of Cryptosporidium presence in biopsies from Lebanese patients with recently diagnosed colonic neoplasia/adenocarcinoma before any treatment. This prevalence was significantly higher compared to 7% of Cryptosporidium prevalence among patients without colon neoplasia but with persistent gastrointestinal symptoms (OR: 4, CI: 1.65–9.6, P = 0.001). When the comparison was done against normal biopsies, the risk of infection increased 11-fold in the group of patients with colon adenocarcinoma (OR: 11.315, CI: 1.44–89.02, P = 0.003). Conclusions This is the first study performed in Lebanon reporting the prevalence of Cryptosporidium among patients with digestive cancer. These results show that Cryptosporidium is strongly associated with human colon cancer being maybe a potential etiological agent of this disease.